2016
DOI: 10.1097/01.ogx.0000511254.16194.96
|View full text |Cite
|
Sign up to set email alerts
|

Modeled Fetal Risk of Genetic Diseases Identified by Expanded Carrier Screening

Abstract: (Abstracted from JAMA 2016;316(7):734–742) As part of routine obstetrical practice, many prospective parents undergo genetic testing to detect carriers of specific inherited recessive diseases. There are recommendations provided by professional organizations to test for a limited number of individual diseases that are in part based on self-reported racial/ethnic backgrounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
2
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 0 publications
2
66
2
1
Order By: Relevance
“…Because of the increasing quality and decreasing cost of genomic technologies, it is now possible to perform pan-ethnic carrier screening for many conditions simultaneously [referred to as expanded carrier screening (ECS) 2 ]. Our previous study of carrier rates in 346 790 patients showed that an ECS panel was expected to identify more pregnancies at risk for serious conditions than ethnic-based panels spanning far fewer genes (4 ), and the American College of Obstetricians and Gynecologists recently recognized ECS as an acceptable strategy for preconception and prenatal carrier screening (5 ). To the extent that these guidelines increase ECS usage, they will have a large clinical impact because it has recently been shown in clinical-utility studies that approximately 80% of couples found to be at risk for severe conditions pursue alternative reproductive options (6,7 ).…”
Section: © 2018 American Association For Clinical Chemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the increasing quality and decreasing cost of genomic technologies, it is now possible to perform pan-ethnic carrier screening for many conditions simultaneously [referred to as expanded carrier screening (ECS) 2 ]. Our previous study of carrier rates in 346 790 patients showed that an ECS panel was expected to identify more pregnancies at risk for serious conditions than ethnic-based panels spanning far fewer genes (4 ), and the American College of Obstetricians and Gynecologists recently recognized ECS as an acceptable strategy for preconception and prenatal carrier screening (5 ). To the extent that these guidelines increase ECS usage, they will have a large clinical impact because it has recently been shown in clinical-utility studies that approximately 80% of couples found to be at risk for severe conditions pursue alternative reproductive options (6,7 ).…”
Section: © 2018 American Association For Clinical Chemistrymentioning
confidence: 99%
“…MFDR was a modeled estimate of the probability that a pregnancy was affected by a condition on the panel (it could be summed across diseases to yield an aggregate MFDR of the panel), whereas an ARC, as used herein, was a couple identified empirically as being at high risk for an affected child. Reported MFDR numbers were calculated as described previously (4,10 ) only patients receiving routine carrier screening and, therefore, excluded those with known family history or infertility. By contrast, the reported couple and ARC counts are raw counts, not necessarily representative of the general US population because of the over-representation of high-risk ethnic groups, infertility patients, and patients with family history of disease.…”
Section: Patient Cohortmentioning
confidence: 99%
“…Other programs in the Middle East have had mixed success. Expanded carrier screening panels are now available for a large number of autosomal recessive genetic conditions [57]. However, in Western countries with mixed ethnic groups it may be more difficult to show utility in universal screening.…”
Section: Clinical Implications Of Identifying Thalassemia Traitmentioning
confidence: 99%
“…A panel test for four severe childhood conditions was developed in a specific Dutch founder population [4] and panel tests designed for Jewish populations now include more than 10 disorders. Commercial providers have started offering panel tests for more than 100 diseases [5]. Expanded carrier tests offer the advantage that a larger proportion of potentially affected fetuses can be recognized [5,6].…”
Section: Preconception Carrier Screeningmentioning
confidence: 99%
“…Commercial providers have started offering panel tests for more than 100 diseases [5]. Expanded carrier tests offer the advantage that a larger proportion of potentially affected fetuses can be recognized [5,6]. A disadvantage, however, is that the person tested does not know the conditions that they can be tested for; therefore, the perceived sense of urgency may be limited and informed decision-making more difficult [7,8].…”
Section: Preconception Carrier Screeningmentioning
confidence: 99%